Blink - Dekker, Ted, 1962- (W Pub. Group, 2002)
An intoxicating tale set amidst the shifting sands of the Middle East, Blink touches on geopolitical conflicts as ancient as the earth itself. The page-turning plot follows a Saudi Arabian princess fleeing a wretched forced marriage for the promised land of America. A brilliant American graduate student discovers a mysterious power-giving him glimpses into the future. Thrown together, they become pawns in a struggle for power and must manipulate the very future in order to save themselves. In his most riveting novel to date, Dekker brings the story to a dramatic climax that will change the future of fiction in the blink of an eye.